Islamic Banking Strategies In Rural Area: Developing Halal Tourism and Enhancing The Local Welfare - Ameraldo, Fedi; Saiful, Saiful; Husaini, Husaini (IKONOMIKA, 2019)
ABSTRACTThe purpose of this study is to analyze the potential contribution of Islamic banking to development of Halal tourism and the enhancement of local community welfare in rural area.The present study employs a critical analytic approach based on extensive review and discussing the possible contribution of Islamic banking to development of Halal tourism and the local communities in rural area.As discussed in the paper there are some strategies for Islamic banking in the rural area. First, Islamic banking can establish special purpose vehicle to run the microfinance scheme in the rural area in order to minimize the potential risks. Second, some financing mechanisms also can be run by the Islamic banks both sources from internal and external resources, such as participatory model – musyarakah and mudharabah and third parties fund – zakah, infaq, sadaqah and waqf.Last, the branchless banking strategy is also proposed but with a certain intermediations should be firstly done by the Islamic banks, such as social and financial intermediation. Keywords Indonesia, Islamic Banking, Halal tourism, Local Welfare